2014
DOI: 10.1007/s40291-014-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SREBP-2 and SCAP Gene Polymorphisms on Lipid-Lowering Response to Atorvastatin in a Cohort of Chilean Subjects with Amerindian Background

Abstract: The G1784C polymorphism of SREBP-2 gene affects atorvastatin response in Chilean subjects with Amerindian background, and may be an important marker for predicting efficacy of lipid-lowering therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
1
8
1
Order By: Relevance
“…Attenuated LDL‐level lowering in response to atorvastatin therapy was demonstrated in patients with another HMGCR polymorphism, rs12916 T allele, indicating an importance of this gene in relation to the statin response . Another study in Chilean patients showed ‐ SREBF2 G1784C polymorphism was associated with attenuated response to atorvastatin (GG had 9% smaller Tc‐level reduction vs GC and 8% smaller reduction vs CC, p=0.015; GG had 15% smaller LDL‐level reduction vs GC and 12% smaller reduction vs CC, p=0.013) …”
Section: Atorvastatinmentioning
confidence: 98%
“…Attenuated LDL‐level lowering in response to atorvastatin therapy was demonstrated in patients with another HMGCR polymorphism, rs12916 T allele, indicating an importance of this gene in relation to the statin response . Another study in Chilean patients showed ‐ SREBF2 G1784C polymorphism was associated with attenuated response to atorvastatin (GG had 9% smaller Tc‐level reduction vs GC and 8% smaller reduction vs CC, p=0.015; GG had 15% smaller LDL‐level reduction vs GC and 12% smaller reduction vs CC, p=0.013) …”
Section: Atorvastatinmentioning
confidence: 98%
“…Another study found SCAP-796I isoform (A allele) is associated with higher LDL in Caucasian female[7]. A study in Chilean hypercholesterolemic individuals demonstrated that rs12487736 were not associated with pharmacogenomic response to atorvastatin[8], however, rs12487736 polymorphism G allele carriers had a significant better hypolipidemic response than AA carriers in an Indian study[30]. Further adjustment for blood lipid parameters barely influenced the significant associations between SCAP polymorphisms and BP, which showed that the associations between SCAP polymorphisms and BP are independent of blood lipid level.…”
Section: Discussionmentioning
confidence: 99%
“…The rs12487736 polymorphism is a common polymorphism located in exon 16. It is associated with obesity and might contribute to the serum levels of cholesterol in different populations[7,8]. The rs12490383 polymorphism was reported to be associated with body mass index (BMI) change[9].…”
Section: Introductionmentioning
confidence: 99%
“…However, subjects evaluated in the PROSPER cohort were mostly elderly with a mean age of 75 years, while individuals enrolled in our study had a mean age more than 20 years younger, a covariate that can define lipid response [49]. Also, the MAFs found in the PROSPER trial were more related to a Caucasian phenotype, contrasting with the Amerindian background reported for Chilean subjects [50]. Ethnicity has been reported to be a decisive factor contributing to control of dyslipidemia [51].…”
Section: Discussionmentioning
confidence: 59%